2007
DOI: 10.2139/ssrn.964967
|View full text |Cite
|
Sign up to set email alerts
|

Intra-Household Gender Disparities in Children's Medical Care Before Death in India

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 28 publications
1
12
0
Order By: Relevance
“…In line with findings from the literature and from related studies undertaken using the 52nd round data (e.g. Hazarika, 2000;Asfaw et al, 2007a), 1.02% of boys are hospitalized compared with 0.62% of girls, and the difference is statistically significant (po0.001). Given hospitalization, however, there is no statistically significant gender difference in the duration of stay in hospital.…”
Section: Sources Of Data and Measurement Of Variablessupporting
confidence: 89%
“…In line with findings from the literature and from related studies undertaken using the 52nd round data (e.g. Hazarika, 2000;Asfaw et al, 2007a), 1.02% of boys are hospitalized compared with 0.62% of girls, and the difference is statistically significant (po0.001). Given hospitalization, however, there is no statistically significant gender difference in the duration of stay in hospital.…”
Section: Sources Of Data and Measurement Of Variablessupporting
confidence: 89%
“…As has been observed by another study, boys are more likely to experience most kinds of injuries and to be involved in behaviours that are highly correlated with injury [ 11 ]. However, this finding could also suggest that girls are highly discriminated against in access to hospital treatment, as one study in India showed [ 12 ]. The higher proportion of girls than boys in some of the facilities located in drier areas was not surprising as the populations in these areas are mainly nomadic pastoralists.…”
Section: Discussionmentioning
confidence: 99%
“…Budget constraints result in more importance being accorded to male health than to female health. 29 Our study found that urban populations expend more on health care of CVDs than rural population. The health care expenditure goes on increasing from the poorest to the richest, the youngest to the oldest, and the least educated to the most educated population.…”
Section: Discussionmentioning
confidence: 51%